2014
DOI: 10.1353/hpu.2014.0135
|View full text |Cite
|
Sign up to set email alerts
|

Unmet medical care and sexual health counseling needs—: a cross-sectional study among university students in Uganda

Abstract: In 2010, unmet medical care and sexual health counseling needs were assessed among students at a Ugandan University. Unmet medical care need was associated with poor mental health, experience of sexual coercion, and poor self-rated health. Unmet sexual health counseling need was significantly associated with being female, coming from an urban area, low social participation, poor mental health status, experience of sexual coercion, poor self-rated health, inconsistent condom use, and having multiple sexual part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 44 publications
(59 reference statements)
1
18
0
Order By: Relevance
“…Our findings revealed that poor mental health and exposure to sexual coercion were independently associated with unmet healthcare and sexual health counselling needs. These findings are similar to those of Kayagaba et al in their study of the general student population at the MUST ( 17 ). Students with poor mental health and exposure to sexual coercion were at higher risk of reporting unmet needs for sexual health counselling services compared to those without such previous experiences.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings revealed that poor mental health and exposure to sexual coercion were independently associated with unmet healthcare and sexual health counselling needs. These findings are similar to those of Kayagaba et al in their study of the general student population at the MUST ( 17 ). Students with poor mental health and exposure to sexual coercion were at higher risk of reporting unmet needs for sexual health counselling services compared to those without such previous experiences.…”
Section: Discussionsupporting
confidence: 92%
“…Youth is a period of sexual exploration, and same-sex attraction may be common in young adults and in student populations ( 14 16 ). Although previous reports suggest that students at the Mbarara University of Science and Technology (MUST) generally have high rates of unmet healthcare needs and unmet sexual health counselling needs ( 17 , 18 ), those with experience of same-sex sexuality had elevated risk for poor health outcomes and unmet healthcare needs compared to the general student population ( 19 ). The findings showed by Agardh et al indicating increased risk for poor mental health, substance abuse, risky sexual behaviour, exposure to sexual coercion, and unmet sexual health counselling needs among students with same-sex sexuality are thus particularly alarming ( 19 ).…”
Section: Introductionmentioning
confidence: 97%
“…In the identified studies, adolescent sexuality was often implicated in mental health responses as reported by participants. Although most adolescents may experience alterations in mood, regardless of sexuality, the identified studies support that adolescents and youth (11-24 years) experience altered mood and emotions in relation to developing sexuality (Agampodi, Agampodi, & Piyaseeli, 2008;Khopkar, Kulathinal, Virtanen, & Säävälä, 2017;Kyagaba, Asamoah, Emmelin, & Agardh, 2014). These included sadness, depression, regret, fear, anxiety, embarrassment, low self-esteem, guilt, shame, and anger (Agampodi, Agampodi, & Piyaseeli, 2008;Aziato, 2016;Bello, 2017;Biney, 2016;Chrisler & Zittel, 1998;Crichton, Okal, Kabiru, & Zulu, 2013;Girod, Ellis, Andes, Freeman, & Caruso, 2017;Kyagaba, Asamoah, Emmelin, & Agardh, 2014;Khopkar, Kulathinal, Virtanen, & Säävälä, 2017;Lahme, Stern, & Cooper, 2018;Ramathuba, 2015;van Reeuwijk & Nahar, 2013).…”
Section: Relationship Of Sexuality and Mental Healthmentioning
confidence: 91%
“…The majority of studies used qualitative descriptive design (n = 8) (Agampodi, Agampodi, & Piyaseeli, 2008;Aziato, 2016;Bello, 2017;Chrisler & Zittel, 1998;Crichton, Okal, Kabiru, & Zulu, 2013;Girod, Ellis, Andes, Freeman, & Caruso, 2017;;Lahme, Stern, & Cooper, 2018;van Reeuwijk & Nahar, 2013), a few studies used quantitative design (n =3) (Khopkar, Kulathinal, Virtanen, & Säävälä, 2017;Kyagaba, Asamoah, Emmelin, & Agardh, 2014;Ramathuba, 2015), and only one study used a mixed method approach (n =1) to examine the association between sexual health and mental health (Biney, 2016). Sample sizes ranged from 11 to 1,954 adolescent girls and boys depending on the research design.…”
Section: Characteristics Of Identified Studiesmentioning
confidence: 99%
See 1 more Smart Citation